Threshold Dynamics of a Semiconductor Single Atom Maser - Liu, Y. -Y.; Stehlik, J.; Eichler, Christopher; Mi, X.; Hartke, T. R.; Gullans, M. J.; Taylor, J. M.; Petta, J. R. (Physical Review Letters, 2017)
We demonstrate a single atom maser consisting of a semiconductor double quantum dot (DQD) that is embedded in a high-quality-factor microwave cavity. A finite bias drives the DQD out of equilibrium, resulting in sequential single electron tunneling and masing. We develop a dynamic tuning protocol that allows us to controllably increase the time-averaged repumping rate of the DQD at a fixed level detuning, and quantitatively study the transition through the masing threshold. We further examine the crossover from incoherent to coherent emission by measuring the photon statistics across the masing transition. The observed threshold behavior is in agreement with an existing single atom maser theory when small corrections from lead emission are taken into account.
CRIS-Team Scopus Importer:2022-06-27